2013
DOI: 10.21832/9781847698896
|View full text |Cite
|
Sign up to set email alerts
|

Revitalising Indigenous Languages

Abstract: Multilingual Matters Discount Order FormMahalo nui loa to the authors of this important book! Ancestral languages are crucial components of healthy indigenous communities. Yet once a language is lost among childbearing adults, it seems impossible to gain it back again. Developing a resource of fluent second language speaking adults is the answer. This work tells how to reach that crucial step -and with very small languages. E ola nā ʻōlelo ʻōiwi a kākou! Kauanoe Kamanā and William H. Wilson, founding members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Consistent with previous data on the association between AS and alcohol consumption [3,11,12,13,15,16,24,25,26], findings showed that the AD group endorsed more severe Physical and Cognitive concerns than the other two groups.…”
Section: Summary Of Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous data on the association between AS and alcohol consumption [3,11,12,13,15,16,24,25,26], findings showed that the AD group endorsed more severe Physical and Cognitive concerns than the other two groups.…”
Section: Summary Of Findingssupporting
confidence: 91%
“…Another interesting result was that patients with A-D reported stronger Social concerns relative to controls and patients with AD, and this result contrasted with a large body of literature indicating that Social concerns are mainly associated to AD, particularly social anxiety disorder, to the anxiety sphere in general [25], fear of negative evaluation and inhibited behavior in public [29], fear and avoidance of public situations and performances [26], anxiety in social interactions and diagnosis of social phobia [7]. It could be hypothesized that alcohol consumption may be a strategy to reduce physiological responses and to avoid fear of negative judgments, as reported by DeHaas and colleagues [15], who found that AS positively correlated with alcohol consumption as a coping strategy aimed to reduce negative emotions in unpleasant situations.…”
Section: Summary Of Findingsmentioning
confidence: 64%
See 1 more Smart Citation
“…Nonetheless, all Sámi languages are considered seriously endangered (see Svonni, 2008; Moseley, 2010). Sámi languages have been revitalised in the past decade in various decrees (Pietikäinen, 2008 a ; Olthuis et al ., 2013; Tanhua, 2014; Pasanen, 2015; Äärelä, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2001); in these 'kohanga reo' ('language nests'), older Maori speakers transmitted the language to the children and, to some extent, to their parents as well. Today, several minority groups use similar systems of 'language nests' for the benefit of keeping their endangered languages alive through education (Ridanpää & Pasanen 2009;Olthuis et al 2013;Pasanen 2015). Behind all this work in New Zealand, there were a small number of people with an ideological commitment to speaking their native language and continuing the Maori cultural heritage (Fishman 1991, 230-250).…”
Section: Introductionmentioning
confidence: 99%